Modulating the hierarchical fibrous assembly of Au nanoparticles with atomic precision - Qi Li (Nature Portfolio, 2018)
Constructing nanoparticle assemblies with atomic precision remains a major challenge in nanoscience. Here, the authors realize atomic‐level control over the 1D, 2D and hierarchical 3D assembly of Au nanoparticles by modulating the site‐specific surface ligands and associated counterions.